Octahedral chalcogenide rhenium cluster complexes with imidazole. (1st June 2019) - Konovalov, Dmitry I.; Ivanov, Anton A.; Vorotnikov, Yuri A.; Smolentsev, Anton I.; Eltsov, Ilia V.; Efremova, Olga A.; Kitamura, Noboru; Mironov, Yuri V.; Shestopalov, Michael A.
Graphical abstract: Two new luminescent cluster complexes [Re6 Q8 (imzH)4 (imz)2 ] (imzH = imidazole) were synthesised via the reaction in molten imidazole pro-ligand. By the reaction of these compounds with hydrohalide acids their di-protonated forms were also obtained. The luminescent properties of the complexes were characterised. Abstract: Reactions of [Re6 Q8 Br6 ] 4−/3− (Q = S, Se) with molten imidazole lead to the formation of two new neutral cluster complexes [Re6 Q8 (imzH)4 (imz)2 ] (imzH = imidazole). The interaction of [Re6 Q8 (imzH)4 (imz)2 ] with hydrohalic acids resulted in cationic complexes [Re6 Q8 (imzH)6 ]X2 (X = Cl, Br). All compounds were characterised by X-ray single-crystal and powder diffraction analyses, elemental analysis, energy dispersive X-ray and IR spectroscopies. The luminescence of the neutral compounds [Re6 Q8 (imzH)4 (imz)2 ] was also studied.